1995
DOI: 10.1016/0014-5793(95)01179-i
|View full text |Cite
|
Sign up to set email alerts
|

Cellular distribution of protein kinase C isozymes in CD3‐mediated stimulation of human T lymphocytes with aging

Abstract: Protein kinase C (PKC) is involved in a variety of cellular responses, such as the expression and secretion of IL-2, the regulation of cytotoxic killing and cell proliferation. It is known that these immune functions are altered with aging. Here, we show that anti-CD3-triggered T cell proliferation is significantly decreased with aging and that H7, an inhibitor of PKC, impairs the anti-CD3-induced T cell proliferation in a differential manner, lymphocytes of healthy young subjects being more sensitive to the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…Defective PKC activation with aging has also been reported by several authors in human monocytes [18,19] and in human T lymphocytes [20,21], and ϳ50% of elderly subjects has significant reduction in PKC activity in B cells [22]. Agerelated impairment of the translocation of PKC is likely to underlie downstream defects in the activation of immune responses in vitro, as diminished generation of cytotoxic effectors, lower production of some cytokines, and reduced proliferative responses, and in vivo, as diminished response to vaccination and increased susceptibility to infections.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…Defective PKC activation with aging has also been reported by several authors in human monocytes [18,19] and in human T lymphocytes [20,21], and ϳ50% of elderly subjects has significant reduction in PKC activity in B cells [22]. Agerelated impairment of the translocation of PKC is likely to underlie downstream defects in the activation of immune responses in vitro, as diminished generation of cytotoxic effectors, lower production of some cytokines, and reduced proliferative responses, and in vivo, as diminished response to vaccination and increased susceptibility to infections.…”
Section: Introductionsupporting
confidence: 63%
“…It is indeed emerging that the defect in PKC activation with aging reflects changes in signals that recruit PKC to the membrane rather than alterations in enzyme levels or intrinsic functional capacity [20,44].…”
Section: Discussionmentioning
confidence: 99%
“…For example, does overexpression of activated Rho regulate the kinase activity of PKC␣? Since we were able to detect this association only in the membrane fraction of cells, it seems likely that the PKC␣ complexed with Rho is in an activated state, as previous studies have indicated that translocation of PKC␣ to the membrane correlates with its activation (16,48). Alternatively, could PKC␣ modulate Rho activity in the cell through direct phosphorylation or indirectly by phosphorylation of a GEF, GDI, GAP, or other intermediate molecule?…”
Section: Discussionmentioning
confidence: 62%
“…These data indicate that impaired expression of the activation marker CD69 in aging by engagement and even by bypassing the TCR. However, reduced activation of lymphocytes from elderly humans seems, therefore, not only to be due to lower expression of CD3 and/or followed by reduced signal transduction (Fulop et al, 1995) after TCR ligation, but also age-related diminished transcription might be involved in our findings (Whisler et al, 1996).…”
Section: Discussionmentioning
confidence: 69%